Concrete vs. Abstract Processing in Repetitive Negative Thinking: Distinct Functional Effects on Emotional Reactivity and Attentional Control - Kornacka, Monika; Krejtz, Izabela; Douilliez, Celine (Frontiers in Psychology, 2019)
Repetitive negative thinking (RNT) is a transdiagnostic process linked to emotional regulation impairment and involved in mood, anxiety, eating disorders and addictions. Attentional disengagement impairment is one of the factors hypothesized to be responsible for the recurrent and uncontrollable character of RNT. The aim of the present study was to empirically test this hypothesis with evaluation of disengagement from negative and RNT-related stimuli separately. Sixty participants were randomly allocated to one of three experimental conditions: abstract RNT, concrete RNT, and control condition (distraction). The change in their negative affect (PANAS) and their attentional disengagement impairment (exogenous cueing task) were measured. The analysis revealed that participants in abstract RNT condition presented higher emotional reactivity comparing to concrete or distraction conditions. The results indicated no differences between induction conditions in attentional disengagement. However, participants after concrete RNT induction had longer mean response times in exogenous cueing task comparing to control induction suggesting that they detected presented stimuli slower than participants in control conditions. The results raised an important, from clinical point of view, question of distinctive impact of two types of RNT on emotional reactivity and attentional processes.